Produk Inovasi Aromaterapi Berbasis Minyak Atsiri Kemenyan, Kamfer Sumatera Dan Ekaliptus - Kholibrina, Cut Rizlani; Aswandi, Aswandi (Jurnal Farmasi Udayana; Vol. 10, No 1, Tahun 2021, 2021)
The global pandemic Covid-19 encourages peoples to improve their immune system. Both healthy food and regular exercise, good immunity can be achieved from healthy and relaxing mind, including through aromatherapy. This is in line with increasing awareness in holistic and organic medicine. The objectives of study are to develop aromatherapy products based-on sumatran camphor, styrax, and eucalypts essential oils; and to identify consumer preferences for innovation products. A conjoint analysis was operated to determine consumer preferences. The active compounds contained in essential oils combination are including a-pinene, 1.8-cineole, limonene, b-caryophyllene and p-cymene. The combination and presence of similar active compound harmonize aroma with minimal contraindications and produce refreshing and relaxing aromas. The 1.8-cineole is known as anti-fungal, antiviral which offer relief to congested respiratory system, thereby boosts immune system. Moreover, p-cymene has been identified to reduce anxiety, nervousness, and relaxing the mind. Based on conjoint analysis, aroma has the greatest influence on consumer preferences. The most preferred profile is aromatherapy product which soft-refreshing aroma, roll-on package, volume 6 ml, at price of Rp 35,000. Aroma is influenced by personal’s perceptions, which related to initial recognition of certain scents as olfactory memory.